Development of an analytical method for determination of lead and cadmium in biological materials by GFAAS using Escherichia coli as model substance - Gende, Michelle; Schmeling, Martina (PLOS ONE, 2022)
In this work, an analytical method was developed for the determination of lead and cadmium in biological samples using graphite furnace atomic absorption spectrometry. Escherichia coli (E. coli) was chosen as model substance for this purpose as it is readily available in most laboratories and can be quickly and easily prepared with a high turnaround rate. Four different sample preparation methods were initially evaluated with respect to percent recovery, limit of detection, and limit of quantification, and the most promising one was developed further. The final process involving microwave assisted digestion of the sample with nitric acid and hydrogen peroxide showed high recovery, repeatability, and specificity. The process was first applied to lead and then extended for the determination of cadmium in the same E. coli substrates. Finally, to validate the process, a certified references material was analyzed, and the results obtained were evaluated with respect to accuracy by comparing them to the reported ones.